Outcome of Functional Endoscopic Sinus Surgery in Patients with Chronic Rhinisinusitis Not Responding to Medical Therapy - Pyakurel, Pradeep Kumar; Paudel, Deepak; Chettri, Shyam Thapa (Journal of College of Medical Sciences-Nepal, 2019)
Background: chronic rhinosinusitis (CRS) is common chronic condition and is treated with antibiotics, nasal irrigation and steroids. Patients who do not respond to medical therapy are subjected to functional endoscopic sinus surgery. The objective of the study is to assess the clinical improvement after functional endoscopic sinus surgery among the patients of chronic rhinosinusitis (CRS) who failed medical management. Methods: A Prospective longitudinal study conducted within a period of 1 year. Patient with CRS who failed with medical management were subjected functional endoscopic sinus surgery (FESS). Pre –operative symptoms score and endoscopic score were assessed and compared with that of post- operative scores at the end of 6 weeks and 12 weeks. Results: Fifty-two patients who completed three months of follow up were included in the study. The mean preoperative VAS symptoms score was 5.7 and was 2.23 after FESS and difference was significant (P <0.01). There was significant improvement of the endoscopic score (ES) after FESS, the mean ES preoperatively was 4.038 and it improved to1.31 at 6 weeks and 0.75 in the 12 postoperative weeks. Post-operative adhesion was the most common complication and occurred in 15% of patients. Conclusions: FESS is a safe procedure. Patients with CRS who don’t respond to medical therapy should undergo this safe surgical procedure FESS with good outcome.